ASSESSMENT OF BETAWI DANCE PRACTICE LEARNING E-ASSESSMENT BASED - Triana, Dinny Devi Triana; Soewardjo, B. Kristiono; Adhi, Bambang P; Budiman, Agus; Taryana, Tatang (LPPM Universitas Negeri Jakarta, 2023)
“Merdeka Belajar Kampus Merdeka” (MBKM) is a policy that prepares students ready for use in various joints of life, thus demanding the competence of students and educators in using and utilizing technology in learning. One of MBKM's policies is a student exchange that is converted to 20 credits. Students are given the authority to take courses at various colleges relevant to the field of science and graduate access. Under this policy, a number of courses that have been converted to the MBKM requirement are of concern, especially in the process of learning and assessment. E-assessment used in assessing the learning process of dance practice courses can be a solution, so that students are monitored and evaluated in their learning progress. E-assessment is applied in Betawi dance courses taught at UNJ and UPI Bandung. Research methods use R&D at the system development stage to obtain input so that the evaluation system on e-assessment can be used easily and measurably. The use of e-assessment is expected to make it easier for lecturers to monitor learning outcomes and convert the values acquired by students.